Rheology, shear zone width, microstructural evolution and tectonics of a zippered strike-slip shear zone: The Senador Pompeu shear zone, northern Borborema Province, Brazil. (January 2023) - Ávila, Carlos F.; Archanjo, Carlos J.; Platt, John P.; Fossen, Haakon
Abstract: Studies of the Borborema Province have broadly elicited the important role of its abundant strike-slip shear zones in accommodating relative motion of crustal blocks during the Brasiliano orogeny, but seldom quantitatively addressed key aspects of shear zone deformation such as longevity, slip rate, total offset, kinematics and rheology. To provide unprecedented level of detail regarding the dextral Senador Pompeu shear zone of northern Borborema Province, we have conducted a complete structural study using detailed geological mapping, deformation microstructures, Electron Backscatter Diffraction (EBSD), geobarometry, and shear zone width modelling. Our results show that: (i) shear zone width decreases systematically along strike from its northern segment, monotonously composed of high-temperature penetrative mylonitic gneisses, towards the south, made up of low-temperature ultramylonites, cataclasites and pseudotachylytes; (ii) quartz deformation microstructures change consistently from high-T grain boundary migration recrystallization and m ⟨ c ⟩ slip in the northern segment, to subgrain rotation/bulging recrystallization, mixed − ⟨ a ⟩ slip and cataclasis in the southern segment; (iii) geobarometry of synkinematic shear zone-bounded plutons indicate a depth difference of c. 10 km over a length of 200 km of the Senador Pompeu shear zone; (iv) shear zone width modelling indicate that slip rates must have been at least 10 mm/yr; (v) geological units show a total offset of 50–75 km; (vi) three dextral closing zipper segments found along the length of the shear zone juxtapose mylonites with opposing kinematics. From the consistent decrease in shear zone width and deformation temperature towards the southwest and the difference in emplacement depth of synkinematic granites we interpret that the northern segment is up-tilted by a few degrees (c. 3°) relative to the southern segment, exposing the strength profile, the brittle-ductile transition and the relation between depth and width of the shear zone. The width simulation carried out on that basis allowed the long-term slip rate to be constrained at >10 mm/yr, from which we interpret that the Senador Pompeu had a short-lived activity of c. 10 Myr (584‒574 Ma). Highlights: Structural and width zonation was identified in the Senador Pompeu shear zone. Geobarometry indicates a tilted crustal section exposing a strength profile. The Senador Pompeu shear zone has a minimum offset of 50–75 km. Shear zone width modelling indicate shear zone longevity was c. 10 Myr. Zippered shear zone segments identified along Senador Pompeu shear zone.